‘Super p53’ mice exhibit enhanced DNA damage response, are tumor resistant and age normally - García-Cao, Isabel (Oxford University Press, 2002)
The tumor suppressor p53 is critical in preventing cancer due to its ability to trigger proliferation arrest and cell death upon the occurrence of a variety of stresses, most notably, DNA damage and oncogenic stress. Here, we report the generation and characterization of mice carrying supernumerary copies of the p53 gene in the form of large genomic transgenes. Prior to this, we demonstrate that the p53 transgenic allele (p53-tg), when present in a p53-null genetic background, behaves as a functional replica of the endogenous gene. ‘Super p53’ mice, carrying p53-tg alleles in addition to the two endogenous alleles, exhibit an enhanced response to DNA damage. Importantly, ‘super p53’ mice are significantly protected from cancer when compared with normal mice. Finally, in contrast to previously reported mice with constitutively active p53, ‘super p53’ mice do not show any indication of premature aging, probably reflecting the fact that p53 is under normal regulatory control. Together, our results prove that cancer resistance can be enhanced by a simple genetic modification and in the absence of undesirable effects.